2019
DOI: 10.1287/isre.2018.0799
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Sin City: An Empirical Study of Craigslist’s Impact on Prostitution Trends

Abstract: Online prostitution has flourished due to presence of online intermediaries. Despite the illegality of selling sexual services online, the Section 230 of Communications Decency Act shields websites from liability for unlawful postings by third parties. Consequently, the websites like Craigslist have become a haven for prostitution-related ads. In this paper, we quantify the economic impact of Craigslist's entry on prostitution incidence, and identify potential pathways in which the website affects the sex indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…While there is research showing a relationship between advertising and website interest, adverts on Backpage are quite different from traditional advertising for political campaigns. With that said, in a study of approximately 2,000 counties in the United States over nine years (1999–2008) with access to Craigslist compared to counties without access, it was found that the use of online web advertisements led to a 17.58% increase in prostitution cases in these counties (Chan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While there is research showing a relationship between advertising and website interest, adverts on Backpage are quite different from traditional advertising for political campaigns. With that said, in a study of approximately 2,000 counties in the United States over nine years (1999–2008) with access to Craigslist compared to counties without access, it was found that the use of online web advertisements led to a 17.58% increase in prostitution cases in these counties (Chan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we contribute to the literature that studies spillovers across physical and digital markets (Liebowitz 2004, Zentner 2006, Smith and Telang 2009, Danaher et al 2010) by adding to the conflicting results of research on cannibalization across these markets. Third, we add to the literature that focuses on how habits and choices are affected by the introduction of new services (Chan et al 2019, Lee et al 2018, Burtch et al 2018, Babar et al 2021. Our work contributes by identifying how and why the prices of physical collectibles are affected by the introduction of NFT collectibles.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our work contributes to the literature that studies how Electronic copy available at: https://ssrn.com/abstract=3921064 the introduction of new services can affect peoples' habits and choices. Studies in this stream have investigated how new platforms can affect prostitution (Chan et al 2019), transportation (Lee et al 2018), and entrepreneurial activity (Burtch et al 2018) trends, as well as meal preparation activities and physical health (Babar et al 2021). Our work expands this stream by studying how and why the introduction of NFT collectibles affects customer choices as reflected by changes in the prices of physical collectibles.…”
Section: Introductionmentioning
confidence: 98%
“…This explanation suggests that if a cheating-enabling environment suddenly becomes easier to access, people may be more willing to choose it not only because of the lack of the additional costs but also because of the favourable comparison to the previous costly state. This effect could have contributed, for example, to greater demand for illegal downloading of movies after the price reduction of a broadband connection (Danaher & Smith, 2014), and to stimulation of prostitution business after a high efficiency of pairing of sex-workers and their clients on websites like Craigslist became available (Chan, Mojumder & Ghose, 2019).…”
Section: Discussionmentioning
confidence: 99%